Toxicity of Lavandula angustifolia oil constituents and spray formulations to insecticide‐susceptible and pyrethroid‐resistant Plutella xylostella and its endoparasitoid Cotesia glomerata. Issue 6 (9th September 2015) - Yi, Chang Geun; Hieu, Tran Trung; Lee, Si Hyeock; Choi, Byeoung‐Ryeol; Kwon, Min; Ahn, Young‐Joon
Abstract: BACKGROUND: Plutella xylostella is one of the most serious insect pests of cruciferous crops. This study was conducted to determine the toxicity of 21 constituents from Lavandula angustifolia essential oil (LA‐EO) and another 16 previously known LA‐EO constituents and the toxicity of six experimental spray formulations containing the oil (1–6 g L −1 sprays) to susceptible KS‐PX and pyrethroid‐resistant JJ‐PX P. xylostella larvae, as well as to its endoparasitoid Cotesia glomerata adults. RESULTS: Linalool and linalool oxide (LC50 = 0.016 mg cm −3 ) were the most toxic fumigant compounds and were 10.7‐fold less toxic than dichlorvos to KS‐PX larvae. Either residual or fumigant toxicity of these compounds was almost identical against larvae from either of the two strains. Against C. glomerata, dichlorvos (LC50 = 7 × 10 −6  mg cm −3 ) was the most toxic insecticide. LA‐EO was ∼1430 times less toxic than dichlorvos. The oil applied as 6 g L −1 spray and emamectin benzoate 21.5 g L −1 emulsifiable concentrate provided 100% mortality against larvae from either of the two strains. CONCLUSION: Reasonable P. xylostella control in greenhouses can be achieved by a spray formulation containing the 6 g L −1 oil as potential contact‐action fumigant. © 2015 Society of Chemical Industry